Perempuan dan Ketahanan Keluarga di Masa Pandemi Covid-19: Studi Kasus Mantan Para Pekerja Perempuan di Kota Bandung - Rika Dilawati; Eni Zulaiha; Yeni Huriani (Journal of Society and Development, 2021)
This paper will discuss the strategies of former female workers who were laid off due to the Covid-19 pandemic in strengthening family resilience. The case study taken is a female worker who is the backbone of a family who is domiciled in the city of Bandung, West Java. This paper uses a qualitative method with data collection through in-depth interviews (indept-interview). This study found that female workers faced a very big dilemma when they lost their jobs and had to take care of their children at home due to online school switching. Thus, women workers are trying to find alternatives to meet the financial needs of their families. Generally they work by selling with a small capital base, and some only expect help from the government while exchanging roles with their husbands. Termination of employment (PHK) experienced by female workers also still leaves gender discrimination, both from the company where she works, educational institutions to community constructs. Women's resilience in carrying out double burdens is proof that they have power over themselves and their families, but when facing a wider environment they are still trapped in a patriarchal culture.